The electrical stimulation of lamp meat - ΓΕΩΡΓΑΚΗΣ Σ.; ΒΑΡΕΛΤΖΗΣ Κ.; ΑΓΑΚΙΔΟΥ Ε.; ΕΛΕΥΘΕΡΙΑΔΟΥ Α. (Journal of the Hellenic Veterinary Medical Society, 2019)
A research of the literature reveals that the tenderness of the meat is affected by its electrical stimulation (ES) when it is taking place under specific conditions. The effect of the electrical stimulation (ES) has been investigated concerning the tenderness ability of lamb as well as the alterations of lactic acid, total creatinine, pH, Water Holding Capacity (WHC) and brightness of the muscle. The psoas major muscles were removed from the sheep carcasses. The right one was under electrocution of 150 V, 23 mA in 50 KHz for 50 sec, 30 min after slaughter. The left one was used as a control muscle. Two samples were taken from the psoas major muscles (sample-control muscle) which were kept in a refreg. temperature wraped up in alluminum foil, directly and 24 hours after the electrocution of the psoas major muscles. It is obvious from the results that: 1. There is no change of the WHC values of the meat between sample and control muscle. 2. The brightness of the meat of the control muscle (GÖFO value) was: GÖFO0 = χ = 85,71 and GÖFO, = χ = 86,28 and the brightness of the meat of the sample was GÖFO0 = χ = 86,00 and GÖFO,. = χ = 85,57. No important difference has been found statistically between GÖFO, value of the control muscle and GÖFOM value of the sample for Z05 value. 3. Total creatinine content (mg/g) was: a) In the control muscle: xn = 0,239±0.093 and x24 = 0,357+0,075 b) In the sample: x0 = 0,276±0,155 and x24 = 0,424+0,202 A real increase of the total creatinine content has been found in the sampple. However, this difference is not statistically significant for Z05 value. 4. The lactic acid content (mg/g) was found out to be: a) In the control muscle: xn = 0,292+0,128 and x24 s 0,422+0,040 b) In the sample: xn = 0,367±0,096 and x24 = 0,544+0,104 There is no important statistical difference between the x24 values of the control muscle and the sample for Z0, value. 5. The pH values ranged as follows; a) In the control muscle: xn = 6,65+0,031 and x24 = 6,07+0,032 b) In the sample: χ70 = 6,54±0,281 and x24 = 6,01±0,307 There is no important statistical difference between the above mentioned values of x24 of the control muscle and the sample. 6. In spite of the fact that the meat had not ripened yet the sample was much tenderer than the control muscle. Generally it is obvious that the electrocution affects to a great extent certain biochemical changes which take place inside the muscle after death. In this way the meat becomes more tender without any indication of it becoming ripened at an accelerating rate. Furthermore, there are changes (relative to the control muscle) in the values of lactic acid content, total creatinine content, GÖFO and pH.